Last Writings for a New Beginning. The Open Legacy of Thomas S. Kuhn: Thomas S. Kuhn, The Last Writings of Thomas S. Kuhn: Incommensurability in Science, Edición de Bojana Mladenović, Chicago: The University of Chicago Press, 2022. xlix + 302 pp. - Ortiz Ayuso, Jesús (Analysis. Journal of Philosophical Research, 2024)
In this text we present a synthesis of the three seccions that make up The Last Writings of Thomas Kuhn: Incommensurability in Science, a volume that collects the latest works of Thomas Samuel Kuhn. The book comprises two fundamental texts from the eighties, “Scientific Knowledge as Historical Product” and “The Presence of Past Science”, as well as the last and unfinished book on which the author would work in the last years of his production, Plurality of Worlds. Along with this synthesis, we review the two key arguments that connect his late stage with the classic work and allow us to praise the transversality of his ideas: knowledge as a historical product and the outline of a theory of meaning.